The Effect of the Snowball Throwing Learning Model on the Learning Outcomes of Grade X Students - Yani, Amiya Linda; Sarkowi, Sarkowi; Irwansyah, Yadri (Civiliza Publishing, Indonesia., 2025)
Education is the main foundation in forming quality and competitive human resources. In the context of learning in schools, the success of the educational process can be measured through the achievement of student learning outcomes. This study aims to examine the effect of the Snowball Throwing learning model on the learning outcomes of class X students at SMAN 5 Lubuklinggau City on the Dongson Culture material. This research method uses a quantitative approach with a pre-test post-test control group design with samples of the experimental class (XE8) and the control class (XE4). Data were collected through multiple choice tests and analyzed using the t-test after first being tested for normality and homogeneity. The results showed a significant effect of the Snowball Throwing learning model on improving student learning outcomes (t-count = 80.09; t-table = 2.021; α = 0.05). The experimental class using the Snowball Throwing model experienced a more significant increase in learning outcomes than the control class using conventional methods. Therefore, the Snowball Throwing learning model is recommended as an alternative effective learning model to improve student learning outcomes in the History subject.